Characteristics of the intracavity dispersion in an erbium-doped fiber laser - Kim, BK; Lee, JC; Jhon, YM; Kim, MW; Kim, SK; Choi, SS; Oh, MS (OPTICAL SOC AMER, 1999)
We have found theoretically that the intracavity dispersion of a laser is independent of the pumping power and wavelength and that the resonant group-velocity dispersion vanishes. We have experimentally observed that the intracavity dispersion of an erbium-doped fiber laser was independent of the pumping power and wavelength within the measuring error, which agrees well with our theoretical predictions. (C) 1999 Optical Society of America.